A brief history of nearly EV‐erything – The rise and rise of extracellular vesicles. Issue 14 (17th December 2021) - Couch, Yvonne; Buzàs, Edit I.; Di Vizio, Dolores; Gho, Yong Song; Harrison, Paul; Hill, Andrew F.; Lötvall, Jan; Raposo, Graça; Stahl, Philip D.; Théry, Clotilde; Witwer, Kenneth W.; Carter, David R. F.
Abstract: Extracellular vesicles (EVs) are small cargo‐bearing vesicles released by cells into the extracellular space. The field of EVs has grown exponentially over the past two decades; this growth follows the realisation that EVs are not simply a waste disposal system as had originally been suggested by some, but also a complex cell‐to‐cell communication mechanism. Indeed, EVs have been shown to transfer functional cargo between cells and can influence several biological processes. These small biological particles are also deregulated in disease. As we approach the 75th anniversary of the first experiments in which EVs were unknowingly isolated, it seems right to take stock and look back on how the field started, and has since exploded into its current state. Here we review the early experiments, summarise key findings that have propelled the field, describe the growth of an organised EV community, discuss the current state of the field, and identify key challenges that need to be addressed.